Portuguese anti-money laundering policy: A game theory approach - Jayantilal, Shital (2017)
The fight against money laundering has taken center stage in the global arena. The European Union (EU), in line with various international organizations, plays an active role in the fight against this crime and promotes anti money laundering directions to its member states. The statistics regarding Portugal (a member of the EU since 1986) indicate that it lags behind most of the EU members in terms of reporting of suspicions of money laundering. This paper adopts a game theory approach to study the efficiency of the combat against money laundering in Portugal, both with regard to the financial and the non financial sector of the economy. Additionally, the paper studies the impact of the increase of sanctions, as recommended by the 4th Directive 2015/849 of the European Parliament and of the Council of 20th May of 2015, on that combat. The results show that the low probability of the institutions being caught (and fined) for not complying with their reporting duties, coupled with the low conviction rates for money laundering crimes, justifies the reduced number of suspicious transactions reported. The findings highlight that an increase of sanctions, on both financial and non financial institutions, would tend to augment the efficiency of the combat against money laundering in Portugal.